The institutionalization and “medicalization” of family planning in Tonga - Henry Ivarature (Asia-Pacific Population Journal, 2000)
This article focuses on the introduction and establishment of family planning in Tonga and argues that family planning has been medicalized. In the process of institutionalizing family planning through the formal medical structure, what has occurred is that women - the focus of this national policy - have had their reproductive and sexual environments medicalized. Also, family planning at the macro level, aside from its clinical and medical objectives, has taken up a regulatory function for the socio-economic and developmental aspirations of the state.